COMPILING OF CONVENTIONAL MEDIA-BASED LANGUAGE GAME BOOK FOR ARABIC BOOK AT MADRASAH TSANAWIYAH MALANG - Mi'rotin, Sholikah; Rosyidi, Abdul Wahab; Arifa, Zakiyah (Abjadia : International Journal of Education, 2024)
Teachers who are joined the deliberation of Arabic subject teacher at Madrasah Tsanawiyah Malang had several problems in Arabic learning which were the students found the Arabic learning process was difficult, some students in grade seven did not graduate from Madrasah Ibtidaiyah or haven’t a prior foundation in Arabic. Therefore, the researcher compiled a language game book to provide illustration to the students that Arabic is an easy and fun lesson. The purpose of this research is: to describe the compiling of conventional media-based language game book for Arabic book, to find out the feasibility of the compiling book, and to find out the effectiveness of the compiling book. Method of the study applied is Research and Development the ADDIE model. The study results: 1) The conventional media-based language game book contains of language game steps. Each game includes the game objectives, time duration, game nature, equipment, game material, game preparation, game procedure, and game example. 2) The developed book is valid for use, reaching a good criterion from a material expert and design expert, and reaching a very good criterion from an Arabic teacher.3) The result of t-count is greater than the value of t-table, which is 5.56 2.16, meaning that Ha is accepted and Ho is rejected hence it can be said that conventional media-based language game book is effective in increasing students’ competence in the Arabic learning at Madrasah Tsanawiyah Malang.